Analisis Hukum Pengalihan Fungsi Hutan Menjadi Tanah Pertanian : Studi Di Kecamatan Lantung Kabupaten Sumbawa - Rizki Yoga Febriyan; H. Arba Arba (Private Law, 2022)
This study aims to determine the factors, processes and status of the transfer of forest functions into agricultural land in Lantung District, Sumbawa Regency. This research is an empirical normative legal research which was analyzed using qualitative descriptive analysis. Based on the results of research, the Lantung District community transferred forest functions due to economic factors, lack of employment opportunities, customary rights, no forest protection and no legal process. The process of transferring forest functions by clearing land which causes its status as illegal cultivation rights and status as property rights. It is hoped that the Sumbawa District Forestry Service will carry out strict supervision of the forest.